The Effectiveness of the Coaching Program for Prisoners at the Narcotics Prison Class IIa Tanjungpinang - Ruseno, Jonet; Ilmiah Rivai, Nur; Septiawan, Armauliza (Future Science, 2025)
This research phenomenon focuses on the implementation of the independence development program run by the Tanjungpinang Class IIA Narcotics Prison. The program run is still considered ineffective, because the perpetrators who are declared to have completed the coaching and released from prison do not immediately or not at all get a job according to the skills learned, coupled with the stigma of society against drug criminals. Therefore, the purpose of this study is to see the extent to which the effectiveness of existing programs for Prisoners of Prison (WBP) can help productivity and awareness of crimes committed. The theory used by researchers in this study is Sutrisno (2007) regarding program effectiveness. The research method used is descriptive qualitative with a case study approach. The results showed that of the 5 existing indicators, achieving goals is an indicator that can provide effective results, as evidenced by the many coaching programs provided to WBP. Meanwhile, the less effective indicator at this time is real change. This is evidenced by the fact that there are still many cases committed by prisoners after leaving the prison and committing the same crime. The conclusion in this study is that various programs related to talent development and skills have been carried out in accordance with the interests and talents possessed by the WBP of the Class IIA Tanjungpinang Narcotics Prison, such as training in planting, farming, and animal husbandry, to carpentry. Thus, providing a variety of programs that can be utilized after leaving the prison.